Stereotactic Ablative Radiotherapy for oligo-progressive disease refractory to systemic therapy in Non-Small Cell Lung Cancer: A registry-based phase II randomized trial (SUPPRESS-NSCLC). (March 2022) - Bahig, Houda; Tonneau, Marion; Blais, Normand; Wong, Philip; Filion, Edith; Campeau, Marie-Pierre; Vu, Toni; Al-Saleh, Afnan; Tehfé, Mustapha; Florescu, Marie; Roberge, David; Masucci, Laura; et al.
Highlights: Treatment of NSCLC patients with oligo-progressive disease on systemic treatment remains controversial. This phase II trial evaluates SABR to all oligo-progressive lesions in combination to current systemic therapy. PFS and OS between patients treated with SABR with continuation of current systemic therapy vs standard of care will be assessed. Intention-to-treat analysis of SABR compared to standard of care will be evaluated. Abstract: Background: Management of Non-Small Cell Lung Cancer (NSCLC) patients with oligoprogression remains controversial. There is limited data to support the strategy of Stereotactic Ablative Radiotherapy (SABR) targeting the oligoprogressive disease in combination with ongoing systemic treatment. We aim to assess the benefit of this approach compared to standard of care in the treatment of oligoprogressive NSCLC. Methods: This phase II study will enroll 68 patients with oligoprogressive NSCLC, defined as 1–5 progressive extracranial lesions ≤5 cm involving ≤3 organs. Patients on active systemic therapy (chemotherapy, immunotherapy, targeted therapy or a combination) will be randomized 1:1 to either continue their current systemic therapy in combination with SABR to all lesions or the standard of care (switch to the next line of treatment, continue same treatment or observation). The co-primary endpoints are progression-free survival (PFS) and overall survival (OS). Secondary endpoints include time to next systemic treatment, patient-reported quality of life, cost effectiveness as well as translational analysis to characterize both adaptive immunity and immunogenic cell death markers in the peripheral blood. Discussion: There is an unmet need to carefully examine the efficacy, safety and quality of life impact of SABR in the context of oligoprogressive disease. The present study will provide higher level randomized evidence on the role of SABR in oligoprogressive NSCLC.